1994
DOI: 10.1021/bi00167a036
|View full text |Cite
|
Sign up to set email alerts
|

Role of the amino-terminal domain in regulating interactions of annexin I with membranes: Effects of amino-terminal truncation and mutagenesis of the phosphorylation sites

Abstract: Phosphorylation of the N-terminal tail by protein kinase C strongly inhibits the ability of bovine or human annexin I to aggregate chromaffin granules by increasing the calcium requirement 4-fold (Wang, W., & Creutz, C. E. (1992) Biochemistry 31, 9934-9936). In the present study three forms of human annexin I truncated in the amino terminus at residue Trp-12, Lys-26, or Lys-29 exhibit dramatic differences in their sensitivities to calcium in a chromaffin granule aggregation assay, while the [Ca2+](1/2)max valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 29 publications
5
62
0
Order By: Relevance
“…For example, it has been shown by several studies that the N-terminal peptide Ac 2-26 mimics the potent antiinflammatory effects of intact annexin I (35). The amino-terminal domain regulates interactions with membranes (37), and is directly involved in binding to S100 proteins (38,39). Most notably, the N-terminal peptide Ac2-12, which in our study appears essential for binding to the novel glycans (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…For example, it has been shown by several studies that the N-terminal peptide Ac 2-26 mimics the potent antiinflammatory effects of intact annexin I (35). The amino-terminal domain regulates interactions with membranes (37), and is directly involved in binding to S100 proteins (38,39). Most notably, the N-terminal peptide Ac2-12, which in our study appears essential for binding to the novel glycans (Fig.…”
Section: Discussionsupporting
confidence: 52%
“…One is the "N-terminal interaction domain," an N-terminal sequence of ϳ40 residues that is unique in annexin A1 and binds several proteins including S100A11, a member of the S100 family (12). Peptides of the N-terminal interaction domain have previously been shown to disrupt interactions of annexins with specific protein ligands, and perhaps most importantly for the present study, the N-terminal domain is required for annexin A1 membrane aggregation activity (20). Therefore, we next employed as a potential function-inhibiting reagent a peptide comprising the N-terminal 1-13 residues of annexin A1.…”
Section: Inhibition Of Plasma Membrane Resealing By Annexin A1-interfmentioning
confidence: 79%
“…These data indicate that calpain I proteolysis of AnxA1 was essential for generating an active AnxA1 product that could activate ERK in HUVEC, and the molecular mass of the active form of ∼33 kDa suggests that the C-terminal fragment is the active peptide. To affirm this finding, we also tested the N-terminal AnxA1 peptide, Ac2-26, that would be generated by calpain 1 cleavage (15) and has been shown previously to mimic the known antiinflammatory functions of the full-length protein (16,17). We found that it was not able to activate endothelial ERK (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Therefore, the N terminus of the active truncated AnxA1 could be between aa 27 and 30. AnxA1 has been shown previously to be cleaved at various sites in the N terminus by a number of proteases, including calpain I and plasmin after Lys-26 and Lys-29 (15), respectively. To test whether the active truncated AnxA1 could be generated by calpain cleavage, fulllength recombinant AnxA1 was treated with human calpain I, and the resulting product was assayed for its ability to activate ERK in HUVEC.…”
Section: Resultsmentioning
confidence: 99%